ANALISIS KOMODITAS UNGGULAN SUB SEKTOR PERKEBUNAN DI KABUPATEN BENGKAYANG PROVINSI KALIMANTAN BARAT - Hidayat, Rakhmad (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2013)
The aims of this research was: (1) to find out the leading commodities in plantation sub sector in Bengkayang District Area, (2) to find out the structure and the production growth of plantation commodities in Bengkayang District Area (2005-2012). Research area was determined purposively in Bengkayang District Area of West Kalimantan. Analysis used in this research is the analysis of Location Quotient (LQ), Dynamic Location Quotient (DLQ), Classic Shift Share and Esteban Marquillas Shift Share. LQ analysis show that the leading plantation commodities in Bengkayang are Peppers, Cacao, cloves and hazelnut. DLQ analysis show that the leading plantation commodities in Bengkayang are coconut and hybrid coconut. The combined of LQ and DLQ analysis show that there are two commodities experiencing repositioning of non leading became the leading commodity in the future, ie Hybrid Coconut and Coconut. The commodities that experienced a repositioning of leading became the non leading in the future are Rubber, Pepper, Cocoa, Clove and hazelnut. While commodities that stil remain non leading in the future is oil palm, coffee and Pinang. Based on the classic shift share analysis, shows that in the period 2005 - 2012, commodities that experienced an increase in real growth in Bengkayang are Rubber, Oil Palm, Cocoa, Clove, hazelnut and Pinang. The highest increase in productivity occurred in Palm Oil and Rubber. Esteban - Marquillas shift share analysis shown that the commodities that have a competitive advantage is oil palm, hybrid coconut, cocoa, cloves and hazelnut. Palm oil has the highest competitive advantage in the amount of 8.565,97 tons. Plantation commodities which has the advantage and can improve the allocation of production growth in the plantation crop are Bengkayang Coffee, Cocoa, Clove, Pecan and Pinang. Cocoa has the highest allocation advantages in increasing farm production in Bengkayang. Cocoa is also a commodity that has a competitive advantage and excellence allocation with the highest positive value. Keywords: Plantation commodities, Leading Commodities, Location Quotient, Shift Share